Code Switching Analysis as Found in Bunga Citra Lestari Youtube Channel - Devi , Ade Parmitha Chandra; Winarta , Ida Bagus Gede Nova; Utami , Ni Made Verayanti (Institut Pariwisata dan Bisnis Internasional, 2023)
The objectives of this study are to determine the various types and functions of code switching. Poplack's (1980) theory defines three forms of code switching in evaluating the data: tag switching, inter-sentential switching, and intra-sentential switching. Moreover, the theory from Appel and Muysken (1987) distinguishes the six functions of code switching are: referential function, directive function, expressive function, phatic function, poetic function, and metalinguistic function. The data source was taken from Bunga Citra Lestari YouTube’s channel entitled Love Story #1 – BCL Sebelum dan Sesudah Ashraf was published on February 12th, 2021. The method that was used to collect the data is the qualitative method. This research found 79 data of code switching. In analyzing the data, intra-sentential switching is commonly used by the participants in the video which found 50 (63,3%) data. Meanwhile, the metalinguistic function is dominantly used which found 32 (40,50%) data for the functions of code switching utterances by the participants. The result of this analysis because both of the speakers, Daniel Mananta and Bunga Citra Lestari are a bilingual person and they often switch the language into other languages because their society also has an acceptable use of English terms.